(untitled) (KULT_online, 2016)
The relatively new discipline of game studies has already experienced first consolidation movements and has developed canonized disciplinary approaches. This volume provides a comprehensive overview of the current state of German and international game studies research. It is divided into the three major themes “game”, “usage”, and “contexts” which are reflected upon vividly and comprehensively by experienced authors. In this process the authors are not limited to approaches situated in media studies; in fact the collection is characterized by its high degree of interdisciplinarity.